Meningkatkan Pemahaman Siswa Materi Gereja sebagai Komunitas dengan Model Discovery Learning Berbantuan Tanaman Hidup Kelas VIII Fase D SLB A Karya Murni - Kristogonus Tadeus; Nerita Setianingtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
The essence of Classroom Action Research is the existence of efforts in the form of actions or interventions carried out in a planned and systematic manner to solve classroom learning problems faced by teachers every day. Borg in Suyanto (1997:8) explains that the main objective of classroom action research is the development of teacher skills based on learning problems faced by teachers in their own classes. The Catholic Church believes that education is one way to implement the teachings of Christ. According to the document Educating in the Present and the Future (Instrumentum Laboris) no. 1b, faith education must not be separated from human education. Faith education and human education must run simultaneously, because the life of faith is one with every aspect of human life. Therefore, it is necessary to develop a learning model that is in accordance with the characteristics, situations and conditions of students. In the context of SLB A Karya Murni, the discovery learning model is in accordance with the characteristics, situations and conditions of students, especially in class VIII phase D. This Classroom Action Research takes the title: "Improving the Understanding of SLB A Karya Murni Class VIII Phase D Students about the Church as a Community Using the Discovery Learning Model Assisted by Living Flower Media". The author hopes that through research it will provide benefits for the author as an educator, students and educational institutions.